An outbreak of rhinovirus infection in a primary school in Shenyang City, China, in 2022 - Yage Wang; Jiayuan Liang; Zhibo Xie; Bing Wang; Jinhua Song; Baicheng Xia; Huiling Wang; Yao Zhang; Ye Chen; Ling Chen; Shi Cong; Yu Liu; et al. (Elsevier, 2024)
Rhinovirus (RV) is a common pathogen that causes respiratory tract infection and can cause outbreaks in hospitals and welfare institutions. A cluster of respiratory diseases occurred in a primary school in Shenyang City, Liaoning Province, China, in 2022. In this outbreak, a total of 31 students had symptoms similar to those of upper respiratory tract infection, mainly cough and sore throat. Among them, 27 throat swabs were collected and identified for respiratory pathogens by TaqMan low-density array (TLDA), quantitative real-time polymerase chain reaction (PCR), reverse transcription-nested PCR and whole-genome sequencing. Out of the 27 specimens, 24 tested positive for RV, and 21 RV viral protein 1 sequences were obtained, of which 15 (71.43%) were identified as RV-A49, while 2 RV-A20 and 4 sequences from 2 specimens were RV-A30 coinfected with RV-C15. In addition, one whole-genome sequence (WGS) of RV-A49 was obtained, and three unique amino acid mutations were found compared to 23 WGS of RV-A49 from GenBank. In conclusion, this outbreak of upper respiratory tract infection is caused by RV, mainly RV-A49.